The Influence of Price, Consumer Taste, and Product Quality on Consumer Satisfaction Seen from a Sharia Management Perspective (Case Study: Sanjai Sil Aur Kuning Bukittinggi) - Maisaroh, Maisaroh; Nurani, Khadijah (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
This research aims to analyze the influence of price, consumer tastes and product quality on consumer satisfaction. This research is classified as quantitative. The approach used in this research is a descriptive quantitative approach. Sampling used the purposive sampling method. The data used is primary data obtained from the owner of Sanjai Sil, Aur Kuning Bukittinggi. Meanwhile, the data analysis technique used is Multiple Linear Regression, which includes the Classic Assumption Test, Instrument Test, Hypothesis Test, Multiple Linear Regression Analysis, Determinance Test. The analysis of this research uses SPSS 16, based on the results of the T and F test hypothesis testing analysis shows that the independent variables (X1, Simultaneously, X3 has no simultaneous effect on the dependent variable (Y) or H0 is rejected with the Sig value. >0.0